PROMOTE HALAL LIFESTYLE WITH DIGITAL TECHNOLOGY ON ISLAMIC BANKING - Fawa'id, Muhamad Wildan; Utama, Yopi Yudha; Yuliani, Yuliani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Lifestyle is the way a person lives his daily life which is influenced by each other's standards, values, and principles. Everyone's standards, values, and principles are different from each other. The purpose of the research is to show the potential of the halal industry, especially the financial sector in Indonesia, that can be worked on. Because the majority of the Indonesian population is Muslim. PT Bank Syariah Indonesia Tbk (BSI) in the first year since the merger in February 2021 made a positive performance. This can be seen from the net profit of Rp 3.03 trillion, up 38.42% year on year (YoY). However, this potential is still inferior to Malaysia which received the highest score in almost all fields in the halal industry in the first position with a value of 207.2 while Indonesia had to settle for fourth place with a value of 68.5 according to the Global Islamic Economy (GIE) 2021 version. Actually Indonesia has a great opportunity to be better than Malaysia if there is good collaboration between three institutions, namely the government as policy makers, banks as implementers in the field and universities as agents of change, researchers and also strategic catalysts.